Avaliação de esperança e resiliência em pessoas em tratamento hemodialítico - Carine Ferreira; Maria Elena Echevarría Guanilo; Denise Maria Guerreiro Vieira da Silva; Natalia Gonçalves; Júlia Estela Willrich Boell; Barbara Leticia Dudel Mayer (Universidade Federal de Santa Maria, 2018)
Aim: to evaluate the hope manifested by people undergoing hemodialysis and its relation with resilience. Method: cross-sectional study, in two hemodialysis units of the metropolitan region of Florianópolis. Sixty people participated in the study, from January to March 2017. Herth's Hope Scale, adapted and validated for the portuguese language and Connor - Davidson Resilience Scale were used as characterization instruments. Spearman's descriptive analysis and correlation coefficient. Results: moderate and positive correlation between hope and resilience (r: 0.470; p <0.01). Females with higher mean values for hope and resilience (M: 44;72; SD: 3,23) and (M: 84,44, SD: 10,66). Those on the waiting list for transplantation obtained lower scores for hope (M: 42,75; SD: 4,76) and for resilience (M: 79,33; SD: 10,54). Conclusion: people on hemodialysis have a disposition to hope and resilience, which suggests a better adaptation to treatment.